Valve-sparing operations after Ross procedure: a single-center experience - Jahanyar, Jama; Arabkhani, Bardia; Zanella, Luca; Kerchove, Laurent de; Tsai, Peter I.; Aphram, Gaby; Mastrobuoni, Stefano; Khoury, Gebrine El (Annals of Cardiothoracic Surgery; Vol 12, No 4 (July 31, 2023): Three Decades of Aortic Valve-Sparing Operations II, 2023)
Background: The Ross procedure has demonstrated excellent long-term results, with restoration of life-expectancy in patients with severe aortic valve dysfunction. However, reintervention after Ross can occur, and herein we describe our center’s experience with redo surgery after previous Ross procedures. Methods: We searched our prospective database for aortic valve-repair and recruited all adult (≥18 years) patients who have undergone valve-sparing root replacements (VSRRs) and/or aortic valve-repair after Ross procedure between July 2001 and July 2022. Univariable logistic regression analysis was performed to identify variables affecting early mortality. Survival, freedom-from-valve-reintervention and freedom-from-aortic regurgitation (AR) grade ≥3 were analyzed with the Kaplan-Meier method. Results: A total of 63 patients were recruited for this study. Indication for reoperation after Ross was aortic aneurysm without AR in 17 (27%), aortic aneurysm with AR in 27 (43%), and isolated AR in 19 (30%) patients. Median follow-up time was 7.82 years. The majority of patients (76%) had undergone the free root technique during their index Ross operation. Cumulative survival, after redo surgery following Ross, was 98.4% [95% confidence interval (CI): 89.3–99.8%] at 1 year, 96.3% (95% CI: 88.2–98.3%) at 5 years, and 92.4% (95% CI: 87.1–98.0%) at 10 years. Freedom-from-reoperation on the aortic valve at 1 year was 98.4% (95% CI: 97.0–99.8%), at 5 years was 96.7% (95% CI: 87.6–99.0%), and 79.7% (95% CI: 71.1–88.3%) at 10 years. Conclusions: Long-term survival after redo surgery following the Ross operation is excellent. The data support our aggressive valve-sparing approach after Ross.